Analisis Kepuasan Pengguna Aplikasi ANBK Menggunakan Metode EUCS - Rahman, Maulana Abdul; Prasetio, Egi Ibnu; Pakaja, Fachrudin (Jurnal Informatika Ekonomi Bisnis, 2025)
Computer-Based National Assessment, also known as ANBK, is a national education evaluation program that was launched as a replacement for the National Exam (UN) in Indonesia. ANBK is used to comprehensively capture the process and quality of learning outcomes from primary and secondary school levels. However, its implementation requires adequate technological infrastructure and a reliable application system to ensure the smooth implementation of the exam in various regions. Thus, it is important to ensure that the ANBK application system is easy to use, efficient, effective and satisfying for all users, including students, teachers and school administrators. The achievement of this research is to investigate the level of user satisfaction and obtain significant variables that have an impact on user satisfaction of the ANBK Application. This research method applies End User Computing Satisfaction (EUCS) in a quantitative way and dissemination of questionnaires to obtain information from the object of research. The population in this research is ANBK users. The population was 50 respondents using saturated sampling technique and questionnaire dissemination was carried out online. The data collected was processed with the Microsoft Excel LTSC program and PLS-SEM operating variable tool. As a result, there are 5 paths tested, H0 is rejected for two variables and H0 is accepted for three variables. There are two variables that have a significant effect on ANBK application user satisfaction, namely: accuracy and timeliness.